2011
DOI: 10.3109/13693786.2011.583285
|View full text |Cite
|
Sign up to set email alerts
|

Microdilution in vitro antifungal susceptibility of Exophiala dermatitidis, a systemic opportunist

Abstract: The in vitro activities of eight antifungal agents were determined against clinical (n = 63 genotype A, n = 3 genotype B) and environmental (n = 2 genotype A, n = 13 genotype B) strains of Exophiala dermatitidis. The resulting MIC(90)s for all strains (N = 81) were, in increasing order, as follows: posaconazole, 0.125 μg/ml; itraconazole, 0.25 μg/ml; voriconazole, 0.5 μg/ml; amphotericin B, 0.5 μg/ml; isavuconazole, 1 μ/ml; caspofungin, 8 μg/ml; anidulafungin, 8 μg/ml and fluconazole, 16 μg/ml. There were no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 21 publications
9
45
2
Order By: Relevance
“…Similar to many other studies, 29,30 VOR showed good activity against the dematiaceous fungi ( N = 27), with an MIC ≤2 mg l −1 in all the isolates tested. Fungisome TM was also effective against these fungi, with an MIC ≤1 mg l −1 in all the isolates tested, except one Phialophora verrucosum isolate.…”
Section: Resultssupporting
confidence: 88%
“…Similar to many other studies, 29,30 VOR showed good activity against the dematiaceous fungi ( N = 27), with an MIC ≤2 mg l −1 in all the isolates tested. Fungisome TM was also effective against these fungi, with an MIC ≤1 mg l −1 in all the isolates tested, except one Phialophora verrucosum isolate.…”
Section: Resultssupporting
confidence: 88%
“…A previous study used Etest to test E. dermatitidis and found that isolates were susceptible to CAS 32 . Other studies using BDM found results similar to ours 33,34 . In agreement with Pfaller et al.…”
Section: Discussionsupporting
confidence: 91%
“…Most of the isolates of E. dermatitidis and E. phaeomuriformis displayed very low MICs of amphotericin B, itraconazole and voriconazole, thus, confirming previous observations from other reports (Kondori et al, 2011;Badali et al, 2011;Fothergill et al, 2009). However, in patient UCL1, 10 out of the 12 sequential isolates showed high MICs (between 4 and 16 mg ml 21 ) of voriconazole, and 11 isolates showed MICs of 2 mg ml 21 of amphotericin B.…”
Section: Antifungal Susceptibility Testingsupporting
confidence: 77%